Pengaruh Aktivitas Fisik Dengan Peningkatan Kadar Asam Urat Dalam Darah Pada Lansia Di RSUD Labuang Baji Sul-Sel - Nurambiya, Nurambiya; Hunyang, Nathalia (Barongko: Jurnal Ilmu Kesehatan, 2023)
One factor that can influence uric acid levels is physical activity. The activities a person does are related to the level of uric acid in the blood. Physical activity such as exercise or physical movement such as housework will reduce uric acid excretion and increase lactic acid production in the body. The aim of this study was to determine the effect of physical activity on increasing uric acid levels in the blood in elderly patients at Labuang Baji Hospital, Sul-sel. The method used is quantitative with a descriptive research design using a cross sectional approach. To determine the relationship between the independent variable and the dependent variable using joint measurements, the population was 34 people. The sample taken for this study used a total sampling technique so that the results were 34 respondents. The data measurement tool used a questionnaire. The results of research carried out in August 2023 at Labuang Baji Regional Hospital, it can be concluded that there is a relationship between physical activity and uric acid levels in the blood in elderly patients at Labuang Baji Regional Hospital with a p value = (0.036 <0.05). Conclusion From this research, there is a relationship between physical activity and increased uric acid levels in the blood in the elderly at Labuang Baji Regional Hospital, South Sulawesi.